2018
DOI: 10.1093/eurheartj/ehy288
|View full text |Cite
|
Sign up to set email alerts
|

Association between systolic blood pressure and dementia in the Whitehall II cohort study: role of age, duration, and threshold used to define hypertension

Abstract: AimsTo examine associations of diastolic and systolic blood pressure (SBP) at age 50, 60, and 70 years with incidence of dementia, and whether cardiovascular disease (CVD) over the follow-up mediates this association.Methods and resultsSystolic and diastolic blood pressure were measured on 8639 persons (32.5% women) from the Whitehall II cohort study in 1985, 1991, 1997, and 2003. Incidence of dementia (n dementia/n total = 385/8639) was ascertained from electronic health records followed-up until 2017. Cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(153 citation statements)
references
References 29 publications
11
136
1
5
Order By: Relevance
“…A fall in BP is known to occur prior to clinical diagnosis of dementia [12]; hence the inverse associations during the first 10 years are probably due to reverse causation and the weaker associations observed beyond 10 years after measurement may be more reliable. The association with dementia is also known to vary by age, with a previous study reporting that BP measurements taken in mid-life, but not later life, are associated with increased risk of dementia [13]. However, similar analyses in our dataset suggest that mid-life BP is at most weakly associated with dementia risk.…”
Section: Discussionsupporting
confidence: 69%
“…A fall in BP is known to occur prior to clinical diagnosis of dementia [12]; hence the inverse associations during the first 10 years are probably due to reverse causation and the weaker associations observed beyond 10 years after measurement may be more reliable. The association with dementia is also known to vary by age, with a previous study reporting that BP measurements taken in mid-life, but not later life, are associated with increased risk of dementia [13]. However, similar analyses in our dataset suggest that mid-life BP is at most weakly associated with dementia risk.…”
Section: Discussionsupporting
confidence: 69%
“…37,38 However, this assumption is complicated by the fact that different studies will find opposing results when examining the same cardiometabolic abnormality. Other studies find that obesity, 40,41 hypertension, 42 diabetes, 43 and high lipids 44 are risk factors for incident dementia. Other studies find that obesity, 40,41 hypertension, 42 diabetes, 43 and high lipids 44 are risk factors for incident dementia.…”
Section: Sensitivity Analysesmentioning
confidence: 95%
“…For instance, some studies have found that abdominal obesity, 11 hypertension, 39 and high lipids 11,35 are protective against risk of dementia. Other studies find that obesity, 40,41 hypertension, 42 diabetes, 43 and high lipids 44 are risk factors for incident dementia. Finally, some studies find no association between any individual cardiometabolic risk factors with incident dementia.…”
Section: Supporting Information Table B)mentioning
confidence: 95%
“…In part, because of research to better understand the observed associations between midlife hypertension and later-life risk of Alzheimer's disease and vascular dementia. (3)(4)(5)(6) There is also increasing recognition that one of the earliest pathological events in the development of Alzheimer's disease is vascular dysregulation. [8] As well as suggestions that some antihypertensives, specifically those that block angiotensin receptor and calcium channel signalling, may have other neurological benefits.…”
Section: Introductionmentioning
confidence: 99%